Analysis of acetal toilet fill valve supply line nut failure. (October 2017) - Timpanaro, Anthony; Scherzer, Ryan; Keifer, Orion P.; Eason, Paul D.
Highlights: The three failure modes tested are all due to over load failure of the acetal nut. The three mechanisms discussed are as follows: (1) Overtightening of the supply line acetal nut, (2) Supply line lateral pull and, (3) Embrittled supply line lateral pull. Failure from overtightening the acetal nut is possible, if a tool is used. Failure from a lateral pull occurred at higher torques when embrittled. Abstract: In recent years, there has been a rise in the number of product liability cases involving the failure of toilet water supply line acetal plastic nuts. These nuts can fail in service, causing water leaks that result in significant property and financial losses. This study examines three possible failure modes of acetal plastic toilet water supply nuts. The three failure modes tested were all due to over load failure of the acetal nut and are as follows: (1) Overtightening of the supply line acetal nut, (2) Supply line lateral pull and, (3) Embrittled supply line lateral pull. Additionally, a "hand-tight" torque survey was conducted. The fracture surfaces and characteristics of these failure tests were examined with Stereo Microscopy and Scanning Electron Microscopy (SEM). The failure modes were compared and contrasted to provide guidance in determination of cause in these investigations.